2013
DOI: 10.1177/0009922813503036
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians’ Knowledge of and Confidence in Their Referrals for Special Education Services in 3- to 5-Year-Old Children

Abstract: Background Children 3 to 5 years old with developmental delays are eligible for special education services. Objective To assess primary care physicians' (PCPs) knowledge, attitudes, and practices regarding their referrals to the special education system on behalf of children 3 to 5 years old. Design/Methods Mail survey of 400 office-based general pediatricians and 414 family physicians in Michigan, fielded in fall 2012 and winter 2013, with a response rate of 44%. The 4-page survey included knowledge quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…7 Given that providers often have difficulties tracking referrals and are frequently unfamiliar with the referral process itself, there are few second chances to address developmental delays when a first opportunity is missed. 8,9 If pediatric providers are to successfully screen and link children, research is clearly needed to determine where the process fails, starting with the provider talking to a family about a child's possible developmental delay and ending with the EI program communicating its findings back to the provider. A small number of qualitative studies with parents have examined their interactions with providers and the question of why they may not follow-up with a recommended EI or other specialty evaluation.…”
mentioning
confidence: 99%
“…7 Given that providers often have difficulties tracking referrals and are frequently unfamiliar with the referral process itself, there are few second chances to address developmental delays when a first opportunity is missed. 8,9 If pediatric providers are to successfully screen and link children, research is clearly needed to determine where the process fails, starting with the provider talking to a family about a child's possible developmental delay and ending with the EI program communicating its findings back to the provider. A small number of qualitative studies with parents have examined their interactions with providers and the question of why they may not follow-up with a recommended EI or other specialty evaluation.…”
mentioning
confidence: 99%
“…3,4 Primary care providers have also reported that they do not understand requirements for services and lack confidence in identifying children between 3 and 5 years of age who may be eligible for special education services (Part B of the Individuals with Disabilities Education Act). 5 Families referred for early intervention have reported a lack of information from providers on what early intervention is and how to obtain services, and this can result in families not following through once a referral is placed. 6 Such difficulties surrounding referrals potentially prevent or delay children's access to critical services.…”
mentioning
confidence: 99%
“…They regularly see children in their early years and therefore have the opportunity to relate children with suspected developmental delay in their practice with appropriate services. However, physicians have acknowledged that they have a role in facilitating children's access to schoolbased special education services, but that they do not fully understand the eligibility requirements for these services, cannot rely on their knowledge or skills, and do not have the skills to identify children who may be eligible for special education services (32,33).…”
Section: Discussionmentioning
confidence: 99%